2016
DOI: 10.1016/j.clon.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Dose-painting Radiotherapy and Radiobiological Guided Optimisation Enhances the Therapeutic Ratio

Abstract: The toxicity for this radiobiological guided dose-painting protocol was low, but we have only treated a small cohort with limited follow-up time. The advantages of this treatment approach should be established in a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The analyzed literature 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 included 323 (23%) patients with National Comprehensive Cancer Network low-risk disease, 509 (37%) patients with intermediate-risk disease, and 517 (38%) patients with high-risk disease. Three studies did not specify the risk group (29 patients, 2.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyzed literature 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 included 323 (23%) patients with National Comprehensive Cancer Network low-risk disease, 509 (37%) patients with intermediate-risk disease, and 517 (38%) patients with high-risk disease. Three studies did not specify the risk group (29 patients, 2.1%).…”
Section: Resultsmentioning
confidence: 99%
“…In 976 patients (70.8%; n = 17 studies), an MRI was used to identify the IDN. From those series, five (488 patients, 35.4%) used magnetic resonance spectroscopy imaging (Choline/creatine-to-citrate ratios >1.4–2) to define the tumor 28 , 29 , 32 , 33 , 45 , three series (116 patients, 8.4%) used 3T MRI, and nine series (438 patients, 31.7%) used mpMRI (with sequences T2W + dynamic contrast enhancement + diffusion-weighted imaging) 31 , 33 , 34 , 35 , 43 , 44 , 46 , 49 , 48 , of which two studies used open MRI 33 , 35 .…”
Section: Resultsmentioning
confidence: 99%
“…For all subvolume geometries investigated, the biological optimisation was feasible without a significant increase in NTCP compared to conventional uniform-dose plans. Uzan et al [54] maximised the TCP of the DIL, identified on quantitative MRI, while satisfying the NTCP limits for grade 2-3 rectal bleeding and grade 3 faecal incontinence. For TCP modeling, it was assumed that all clonogens are located uniformly inside the DIL with a constant clonogen density and any clonogens outside the DIL can be controlled by the dose to the clinical target volume (CTV).…”
Section: Biological Optimisation Of Prostate Imrt Using Population-bamentioning
confidence: 99%
“…5 In the study development phase, patients had PET/CT imaging at planning whilst on ADT ("ADT group"). As visual tracer uptake was noted to be low for the first 10 patients, subsequent patients had PET/CT imaging at staging before ADT ("ADT-naïve group").…”
Section: Introductionmentioning
confidence: 99%
“…Cohort studies have demonstrated outcomes without increased toxicity. [2][3][4][5] These DILs have been contoured using a co-registered multiparametric MRI (mpMRI) in several studies such as Dose EscaLation to Intraprostatic tumour Nodules in localised prostate Cancer (DELINEATE) (ISRCTN04483921), Hypofractionated External beam Image-Guided Highly Targeted radiotherapy (HEIGHT) (NCT01411332) and Focal Lesion Ablation Microboost In Prostate Cancer (FLAME) trials. 6 An alternative imaging modality for identifying lesions is the positron emission tomography CT scan (PET/CT).…”
Section: Introductionmentioning
confidence: 99%